Impact of Globalization on Communication and Culture: the Indian Scenario (Glocalism: Journal of Culture, Politics and Innovation, 2021)
Globalization in the contemporary world has changed its nature, form and shape expeditiously. Accordingly, its impact is not also limited to economic phenomenon only but has transmitted in all other aspects of life. It is very liquid in nature that changes its form very quickly. Along with it also changes the other phenomenon associated with it like the cultural, structural and societal issues etc. The communication technologies act as a carrier in this regard. It carries out all the transformations occurring in a society to a global level and thus plays a very important role in creating cultural homogenization, differentialism and cultural convergence in the societies. It not only acts as a mirror like reflective process to unleash the old and new forms of inequalities present in the society, but also enhance the levels of modernity in the society.
Keywords: globalization; Indian society; communication technologies; material culture; non-material culture